PHYTOCHEMICAL SCREENING OF METHANOL EXTRACT OF JAMBLANG (Syzygium cumini L.) AS ANTIDIABETIC - Qurratu Aini, S.Si., M.Pd.; Suwarniati Suwarniati; Ira Mirza (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2022)
Jamblang (Syzygium cumini L.) is one of the traditional Acehnese plants that has many health benefits. The purpose of this study was to determine the results of phytochemical screening on the methanol extract of jamblang peel (Syzygium cumini L.) which has the potential as antidiabetic. This study used a qualitative descriptive research design to determine the results of phytochemical screening. Phytochemical screening was carried out using several reagents, with the types and levels adjusted to the type of phytochemical test. Phytochemical tests carried out included: tests for alkaloids, flavonoids, polyphenols, saponins, tannins, terpenoids, and essential oils. The results showed that there were alkaloids (mayer formed a white precipitate, Wagner formed a brown precipitate, Dragendorff formed a red precipitate), terpenoids formed a red precipitate, saponins formed a foam, flavonoids formed a red color, phenolics formed a green color and tannins formed a white precipitate. Flavonoids are antioxidant compounds that are able to ward off free radicals. One of the derivatives of these flavonoids is quercetin and kompferol which are thought to act as antidiabetic because they can repair damage to pancreatic beta cells.Keywords: Phytochemical Screening, Methanol Extract of Jamblang Bark (Syzygium cumini L., Antiabetic.